Алгоритмизированная математическая модель линейного импульсного электродвигателя как ударного источника слабых сейсмических колебаний - Милых, В.И.; Ткаченко, С.В. (Електротехніка і електромеханіка, 2011)
A linear impulsive electric motor, creating small seismic oscillations for a search of minerals, is presented. His mathematical model, which corresponds to the shock power impulse mode, is formulated. The algorithm is developed for numeral realization of this model and the example of his calculation use is shown.